PENINGKATAN HASIL BELAJAR MURID PADA PEMBELAJARAN IPAS MELALUI MODEL PROJECT BASED LEARNING (PJBL) DI KELAS V SD NEGERI 09 2X11 KAYUTANAM - Maylanda, Refina; Zahara, Leni; Hamimah; Zainil, Melva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In Grade V at SD Negeri 09 2 X 11 Kayutanam, this project sought to enhance students' learning outcomes in Science and Social Studies (IPAS) by using the Project Based Learning (PjBL) approach. The research included both quantitative and qualitative methods from Classroom Action Research. Two rounds of planning, carrying out, observing, and reflecting comprised the study. The study included seventeen fifth graders. Documentation, learning outcome assessments, and observation sheets were used to gather data, which was then evaluated using both quantitative and qualitative methods. Students' learning results and the quality of their learning were both significantly improved once the PjBL paradigm was implemented, according to the findings. In Cycle II, the lesson preparation score jumped to 97% from 91.5% in Cycle I. In addition, there was an increase from 85.74% in Cycle I to 92.34% in Cycle II in terms of students' learning outcomes. Students were more actively involved in meaningful learning experiences via project work, teamwork, problem solving, and knowledge production, all of which contributed to the improvement in the PjBL model. As a result, primary school pupils' performance on IPAS assessments improved after using the Project Based Learning paradigm.